Should subsidies to urban passenger transport be increased? A spatial CGE analysis for a German metropolitan area - Stefan Tscharaktschiew; Georg Hirte (Technische Universität Dresden, Fakultät Wirtschaftswissenschaften, 2011)
The objective of this paper is to examine efficiency, distributional, environmental (CO2 emissions) and spatial effects of increasing different kinds of transport subsidies discriminating between household types, travel purposes and travel modes. The effects are calculated by applying a numerical spatial general equilibrium approach calibrated to an average German metropolitan area. In extension to most studies focusing on only one kind of subsidy, we compare the effects of different transport subsidies within the same unified framework that allows to account for two features not yet considered simultaneously in studies on transport subsidies: endogenous labor supply and location decisions. Furthermore, congestion, travel mode choice, travel related CO2 emissions and institutional details regarding the tax system in Germany are taken into account. The results suggest that optimal subsidy levels are either small or even zero. While subsidizing public transport is welfare enhancing, subsidies to urban road traffic reduce aggregate urban welfare. Concerning the latter it is shown that making investments in urban road infrastructure capacity or reducing gasoline taxes may even be harmful to residents using predominantly automobile. In contrast, pure commuting subsidies hardly affect aggregate urban welfare, but distributional effects are substantial. All policies contribute to urban sprawl by raising the spatial imbalance of residences and jobs but the effect is relatively small. In addition, the policies induce a very differentiated pattern regarding distributional effects, environmental effects and benefits of landowners.
Keywords: H24; R13; R14; R20; R48; R51; 330; urban general equilibrium model; transport policy; transport subsidy; commuting